Plant density and growth regulator applications in a tomato crop for industrial processing - Carvalho, Fábio José; Carneiro, Lorena Braz; Benett, Cleiton Gredson Sabin; Benett, Katiane Santiago Silva; Martins, Anne Silva; Silva, Amanda Tavares da; Seleguini, Alexsander (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Growth regulators are used in agriculture to reduce vegetative growth, promote flowering and fruiting processes, and regulate production alternations. In this study, the effects of the use of paclobutrazol (PBZ) and different plant arrangements on the development and productive yield tomatoes grown for industrial use were evaluated. This experiment was carried out in the experimental area of the Universidade Estadual de Goiás, in a randomized block design with a 2×5 factorial arrangement (presence of PBZ and absence of PBZ in seedlings × planting spacing), with four replications and ten plants per plot. The paclobutrazol (growth regulator) applications were carried out in seedlings 15 days after emergence by applying 3.5 mL of the solution per tray at a concentration of 42.5 mg L-1 using a commercial product containing 25% of the active ingredient for the solution. The spacings were 0.15, 0.20, 0.25, 0.30, and 0.35 m between plants and 1.4 m between rows, corresponding to populations of 47,619; 35,714; 28,714; 23,809 and 20,408 plants/ha, respectively. The initial growth and development of the seedlings, characteristics related to productivity, and the physical and chemical quality of fruits harvested in each experiment were evaluated. It was observed that the application of paclobutrazol influenced the phylotechnical characteristics and technological quality of tomato fruits grown for industrial processing. The planting spacings between 0.21 and 0.27 m had better crop development and productivity.